2022
DOI: 10.3389/fneur.2022.1038735
|View full text |Cite
|
Sign up to set email alerts
|

Associations between risk of Alzheimer's disease and obstructive sleep apnea, intermittent hypoxia, and arousal responses: A pilot study

Abstract: ObjectivesObstructive sleep apnea (OSA) may increase the risk of Alzheimer's disease (AD). However, potential associations among sleep-disordered breathing, hypoxia, and OSA-induced arousal responses should be investigated. This study determined differences in sleep parameters and investigated the relationship between such parameters and the risk of AD.MethodsPatients with suspected OSA were recruited and underwent in-lab polysomnography (PSG). Subsequently, blood samples were collected from participants. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Sixty‐seven papers were further excluded after screening titles and abstracts, leaving 10 citations for full‐text review. Three papers were subsequently excluded for the following reasons: One study defined OSA using a questionnaire (Huang et al., 2021 ); another study divided patients into normal‐to‐moderate and severe OSA groups (Tsai, Liu, et al., 2022 ); one study did not group by OSA severity (Tsai, Wu, et al., 2022 ). At last, seven papers were considered eligible for the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixty‐seven papers were further excluded after screening titles and abstracts, leaving 10 citations for full‐text review. Three papers were subsequently excluded for the following reasons: One study defined OSA using a questionnaire (Huang et al., 2021 ); another study divided patients into normal‐to‐moderate and severe OSA groups (Tsai, Liu, et al., 2022 ); one study did not group by OSA severity (Tsai, Wu, et al., 2022 ). At last, seven papers were considered eligible for the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A PRISMA flow diagram of the study selection process is presented in ( Tsai, Wu, et al, 2022). At last, seven papers were considered eligible for the meta-analysis.…”
Section: Searching Resultsmentioning
confidence: 99%
“…A related study reported a significant association between a high mean AHI and increased neurochemical biomarker levels in patients with OSA without dementia [ 29 ]. Another study analyzed PSG parameters and neurochemical biomarker levels and suggested that the elevated AHI, ODI-3%, and arousal indexes were significantly associated with the risk of AD [ 30 ]. OSA acts in synergism with neurochemical biomarkers (i.e., Aβ 42 and T-tau), and patients with mild cognitive impairment having untreated OSA may have shorter progression time to AD compared with those with only mild cognitive impairment [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…These traits interact with each other and contribute to the periodic repetition of respiratory or frequent arousal events in patients with OSA. Recent studies have demonstrated that one of the endophenotypic traits, namely low-ArTH OSA, which may contribute to the highly frequent arousal response, may be associated with or even aggravate other related diseases (e.g., periodic limb movements, cognitive impairment, Alzheimer’s disease) [ 28 , 29 , 30 ]. Therefore, understanding the mechanisms underlying these endophenotypic OSA traits could help to prevent the disease presentation or allow for precise OSA treatment based on the specific pathophysiological condition of each individual.…”
Section: Discussionmentioning
confidence: 99%